Utility of TMS to understand the neurobiology of speech - Murakami, Takenobu; Ugawa, Yoshikazu; Ziemann, Ulf (Frontiers in Psychology, 2013)
According to a traditional view, speech perception and production are processed largely separately in sensory and motor brain areas. Recent psycholinguistic and neuroimaging studies provide novel evidence that the sensory and motor systems dynamically interact in speech processing, by demonstrating that speech perception and imitation share regional brain activations. However, the exact nature and mechanisms of these sensorimotor interactions are not completely understood yet. Transcranial magnetic stimulation (TMS) has often been used in the cognitive neurosciences, including speech research, as a complementary technique to behavioral and neuroimaging studies. Here we provide an up-to-date review focusing on TMS studies that explored speech perception and imitation. Single-pulse TMS of the primary motor cortex (M1) demonstrated a speech specific and somatotopically specific increase of excitability of the M1 lip area during speech perception (listening to speech or lip reading). A paired-coil TMS approach showed increases in effective connectivity from brain regions that are involved in speech processing to the M1 lip area when listening to speech. TMS in virtual lesion mode applied to speech processing areas modulated performance of phonological recognition and imitation of perceived speech. In summary, TMS is an innovative tool to investigate processing of speech perception and imitation. TMS studies have provided strong evidence that the sensory system is critically involved in mapping sensory input onto motor output and that the motor system plays an important role in speech perception.